Nanoscale electrochemical visualization of grain-dependent anodic iron dissolution from low carbon steel. (1st February 2020) - Yule, L.C.; Shkirskiy, V.; Aarons, J.; West, G.; Shollock, B.A.; Bentley, C.L.; Unwin, P.R.
Abstract: The properties of steels and other alloys are often tailored to suit specific applications through the manipulation of microstructure ( e.g., grain structure). Such microscopic heterogeneities are also known to modulate corrosion susceptibility/resistance, but the exact dependency remains unclear, largely due to the challenge of probing and correlating local electrochemistry and structure at complex (alloy) surfaces. Herein, high-resolution scanning electrochemical cell microscopy (SECCM) is employed to perform spatially-resolved potentiodynamic polarisation measurements, which, when correlated to co-located structural information from electron backscatter diffraction (EBSD), analytical scanning electron microscopy (SEM) and scanning transmission electron microscopy (STEM), reveal the relationship between anodic metal (iron) dissolution and the crystallographic orientation of low carbon steel in aqueous sulfuric acid (pH 2.3). Considering hundreds of individual measurements made on each of the low-index planes of body-centred cubic (bcc) low carbon steel, the rate of iron dissolution, and thus overall corrosion susceptibility, increases in the order (101) < (111) < (100). These results are rationalized by complementary density functional theory (DFT) calculations, where the experimental rate of iron dissolution correlates with the energy required to remove (and ionise) one iron atom at the surface of a lattice, calculated for each low-index orientation. Overall, this study further demonstrates how nanometre-resolved electrochemical techniques such as SECCM can be effectively utilised to vastly improve the understanding of structure–function in corrosion science, particularly when combined with complementary, co-located structural characterisation (EBSD, STEM etc .) and computational analysis (DFT).